An agar–polyvinyl alcohol hydrogel loaded with tannic acid with efficient hemostatic and antibacterial capacity for wound dressing. Issue 18 (25th August 2022) - Cheng, Can; Peng, Xu; Xi, Linjie; Wan, Chang; Shi, Shubin; Wang, Yuhang; Yu, Xixun
Abstract : Rapid hemostasis, antibacterial effect and promotion of wound healing are the most important functions that wound dressings need to have. Abstract : Rapid hemostasis, antibacterial effect and promotion of wound healing are the most important functions that wound dressings need to have. In this work, we designed and prepared a hydrogel with antibacterial effect, hemostatic ability and wound healing promotion using agar, polyvinyl alcohol (PVA) and tannic acid (TA). We performed a series of tests to characterize the structure and properties of AGAR@PVA–TA hydrogels. The results showed that the AGAR@PVA–TA hydrogels had good mechanical properties and excellent antibacterial ability as well as good hemocompatibility. The cytotoxicity results showed that the AGAR@PVA–TA hydrogels had good cytocompatibility. And the TA loaded hydrogels also presented some good performances in animal studies. In the liver hemostasis model, the AGAR@PVA–TA hydrogel showed good hemostatic ability. Also, the AGAR@PVA–TA hydrogel was able to promote wound healing in an S. aureus -infected rat wound model. More importantly, our research results demonstrated that compared to other polyphenols (such as proanthocyanidins), TA could better improve the mechanical properties, antibacterial ability and rapid hemostasis of hydrogels, which illustrated the uniqueness of TA. Therefore, the TA loaded hydrogel (AGAR@PVA–TA hydrogel) has the potential to be applied as a wound dressing.